Diseases of the Ocular Surface Associated with Eyelid Makeup and Eyelash Extensions. Clinical Examples - V. N. Trubilin; E. G. Poluninа; D. V. Andzhelova; S. G. Kapkova; V. V. Kurenkov; K. V. Chinenova (Oftalʹmologiâ, 2019)
The environmental factors influence, quite often, negatively affects the state of health. Many of them, such as smoking, deterioration in ecology, uncontrolled alcohol intake, are in detail studied in terms of harm to a human body. Nevertheless, new technologies which action is insufficiently studied, are actively introduced into modern life. So, the use of cosmetology procedures can be a striking example. Now the prevalence of such procedures as eyelash extension, a permanent make-up a century, botulotoxin injections in a periorbital zone, assumes a wide scale. In foreign and domestic literature there are more and more messages about development of the complications which arose owing to use of the above-stated procedures. There are two clinical examples from our practice in this article. They demonstrate the complications which arose after holding a procedure of eyelash extension — acute toxic-allergic conjunctivitis and after a permanent make-up — a chemical burn of a cornea. In these clinical cases of a complication arose due to aggressive action of a chemical basis of the glue applied at eyelash extension and cream-anesthetic which is applied on eyelids before a permanent make-up a century. Treatment of patients included antiinflammatory, antihistaminic, antibacterial therapy and also a long course of the tear replacement therapy applied as keratoproteсtive therapy and for prevention of development of a dry eye syndrome. Considering scales of prevalence of cosmetology procedures in recent years, it is necessary to inform specialists and patients on potential risk of development of the complications connected with the above-stated procedures. The clinical examples given in the article and literature data, demonstrate that in case of cosmetology procedures complications it is necessary to carry out timely rendering the qualified medical ophthalmologic care. It is connected with the fact that, quite often, the cosmetology manipulations, even positioned as harmless, in particular, a permanent make-up of eyelid and eyelash extension can lead to heavy complications, up to vision loss.